Pelatihan Teknologi Digital Dalam Pengembangan Bisnis Berbasis Smart Entrepreneur Model bagi UMKM SigekArt Silungkang Kota Sawahlunto - Ramadhan, Muhammad Fikri; Stefvany, Stefvany (Jurnal Pengabdian UNDIKMA, 2024)
This service activity aims to increase knowledge and skills in financial management based on digital technology in business development for SigekArt MSMEs. The method of implementing this community service uses training, which consists of several stages, namely activity administration, digital business management assistance and product innovation. The results of this service show that the understanding of partner business management has increased, especially in digital financial management. Partners are also able to increase production by more than 85% per day. The quality of production stitching is also better and neater, because the PKM team provides business capital and industrial sewing machine equipment to partners. Product innovation can also be carried out by partners because there is always assistance from the PKM team.